Characterisation of fatigue crack tip field in the presence of significant plasticity. (October 2019) - Lin, B.; Alshammrei, S.; Wigger, T.; Tong, J.
Highlights: Full-field near-tip deformation obtained by DIC and integrated FE. Non-linear characteristics verified by poor fit to William's regression. CODs measured by DIC and integrated FE. A "knee" captured in CODs does not impact on J-integral. Abstract: Characterisation of a fatigue crack tip in the presence of significant plasticity has been challenging due to the lack of suitable tools and lack of knowledge of material constitutive information under cyclic loading. In this paper, Digital Image Correlation (DIC) and integrated finite element (FE) analyses have been used to characterise the crack-tip field beyond the small-scale yielding (SSY) regime in a stainless steel 316L of a compact-tension (CT) specimen under mode I loading conditions. The non-linear characteristics of the near-tip deformation field were verified by the poor fit to the William's regression and the overestimation of the stress intensity factor K. The extent of the crack tip plasticity was estimated using a detailed constitutive material model and compared with the estimated by Irwin. The displacement fields local to a stationary fatigue crack were mapped using DIC, and inputted into the FE model as boundary conditions so that an integrated FE analysis was carried out. Fatigue pre-cracking was simulated in the FE analysis prior to the full-field analysis of the fatigue crack tip, including stress/strain distributions ahead of the crack tip and the crack opening displacement (COD) under selected loading conditions. Although a distinct "knee" was captured as an indication of crack opening from the compliance curves in both the DIC measurements and the FE analyses, consistent with the existing knowledge on the phenomenon of crack closure, it does not appear to correlate with the crack driving force measured by the J-integral.